An intersectional perspective on the entrepreneurial intention of female Ukrainian migrants and refugees - Jolanta Maj; Alexandra David; Aneta Hamza-Orlinska; Maciej Filipowicz; Sabina Kubiciel-Lodzińska (International Entrepreneurship Review)
Objective: The objective of the article is to examine potential variations among migrants from Ukraine concerning their entrepreneurial intention, considering the nature of migration (economic or forced) and their motherhood.